(untitled) (Research, Society and Development, 2022)
This in vitro study aimed to analyze the fracture strength and failure pattern of flared bovine roots restored with different intraradicular fiber posts and core materials, without a ferrule. To conduct this study fifty bovine incisor roots were treated endodontically, and divided into five groups (n=10), according to the following fiber post techniques and core materials: prefabricated fiberglass post and full-body bulk-fill resin composite (PF-BF); prefabricated fiberglass post and dual function resin cement (PF-RC); direct anatomic post and full-body bulk-fill resin composite (AP-BF); CAD-CAM integrated fiberglass post-and-core (CAD-PC); and adjustable fiberglass post and full-body bulk-fill resin composite (AD-BF). Intraradicular fiber posts were cemented with dual functional resin cement (Allcem Core, FGM), restored with CAD-CAM composite crowns (Brava, FGM), and subjected to loading. The data were analyzed by generalized linear models (p <0.05). It was revealed that AP-BF presented lower fracture strength values compared with PF-RC (p=0.006) and AD-BF (p=0.013). Fractures involving the apical third only in CAD-PC. PF-RC presented only failure patterns involving the core restoration or were limited to the cervical third. PF-RC and AD-BF presented higher failure patterns limited to the core restoration, compared with other groups (60% and 50% respectively). Fractures involving the middle third were observed in the PF-BF, AP-BF, CAD-PC, and AD-BF groups. In conclusion, most of the intraradicular fiber post techniques used, and different core materials presented similar fracture strength values. CAD-CAM integrated fiberglass post-and-core presented more fractures involving the middle and apical thirds than the other groups.